Socket-shield and immediate implantation - Khalil, Joseph (2016)
Introduction - After tooth extraction, the alveolar bone undergoes a remodeling process, wich leads to horizontal and vertical bone loss. These resorption processes complicate dental rehabilitation, particularly in connection with implants. Various methods of guided bone regeneration have been described to retain the original dimension of the bone after extraction. Most procedures use filler materials and membranes to support the buccal plate and soft tissue, to stabilize the coagulum and to prevent epithelial ingrowth. It has also been suggested that resorption of the buccal bundle bone can be avoided by leaving a buccal root segment (socket-shield technique) in place, because the biological integrity of the buccal periodontum remains untouched. This method has also been decribed in connection with immediate implant placement. Objective - This literature review aim enumerate and describe the different treatments and tissue reactions after tooth extraction, immediate and delayed implantation. The socketshield technique, the evolution in tooth extraction and immediate implantation with high esthetic results due to the preservation of hard and soft tissues by leaving a buccal root segment in place. Materials and methods - For this purpose a research has been done and data was obtained from on-line resources: Medline, Pubmed, Scielo, Bireme, Bon, books and specialized magazines which was conducted between January 2016 and May 2016. A number of articles have been obtained in English and French ,published between 1997 and 2015 . The key words used were implantology, dental implant, hard/soft tissue, tooth extraction, immediate implantation, delayed implantation, socket-shield. Conclusion - In socket-shield technique, there were neither functional nor aesthetic changes in soft and hard tissues. It’s already a routine practice in the arsenal of highaesthetic immediate implantology and should be used when indicated. Although this technique is quiet promising, we should be aware of the incoming publications about a larger follow up and the predictability of leaving a fragment inside the socket after an extraction.